Phytoestrogen coumestrol improves mitochondrial activity and decreases oxidative stress in the brain of ovariectomized Wistar-Han rats - Ana C. Moreira; Ana M. Silva; Ana F. Branco; Inês Baldeiras; Gonçalo C. Pereira; Raquel Seiça; Maria S. Santos; Vilma A. Sardão (Journal of Functional Foods, 2017)
After the cessation of estradiol (E2) production by the ovaries, mitochondrial function is affected in several organs, as demonstrated in animal models of menopause. Coumestrol is a phytocompound belonging to the coumestan family, showing higher binding affinity for estrogen receptors beta (ERβ) and stronger estrogenic activity. The objective of this work was to compare, for the first time, the effects of coumestrol with E2 regarding brain and liver mitochondrial function in 16-week old ovariectomized Wistar-Han rats (OVX rats). OVX animals were treated with a single administration of 30 μg/kg E2 or coumestrol for 24 h, and mitochondrial function and oxidative stress endpoints were analysed in brain and liver fractions. Obtained results in this study demonstrated that coumesterol is able to improve mitochondrial function in a rodent model with low estrogen levels, most likely due to its modulating effect on mitochondrial respiration and oxidative stress.